2011
DOI: 10.1242/dev.053652
|View full text |Cite
|
Sign up to set email alerts
|

Polycomblike 2 facilitates the recruitment of PRC2 Polycomb group complexes to the inactive X chromosome and to target loci in embryonic stem cells

Abstract: SUMMARYPolycomb group (PcG) proteins play an important role in the control of developmental gene expression in higher organisms. In mammalian systems, PcG proteins participate in the control of pluripotency, cell fate, cell cycle regulation, X chromosome inactivation and parental imprinting. In this study we have analysed the function of the mouse PcG protein polycomblike 2 (Pcl2), one of three homologues of the Drosophila Polycomblike (Pcl) protein. We show that Pcl2 is expressed at high levels during early e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 73 publications
5
74
0
Order By: Relevance
“…In contrast, H3K27me3 was only mildly affected by the level of chromatin-bound MTF2 (Fig. 4e, f), which is similar to the previously observed minor consequences on H3K27me3 levels after MTF2 or PHF19 depletion in vivo 9,10 (Extended Data Fig. 5c).…”
supporting
confidence: 89%
“…In contrast, H3K27me3 was only mildly affected by the level of chromatin-bound MTF2 (Fig. 4e, f), which is similar to the previously observed minor consequences on H3K27me3 levels after MTF2 or PHF19 depletion in vivo 9,10 (Extended Data Fig. 5c).…”
supporting
confidence: 89%
“…One possibility is that other elements within the Xist transcript also bind directly to core PRC2 components. A further study demonstrated that Polycomblike2 (PCL2), a substoichiometric component of PRC2, is important for PRC2 recruitment by Xist RNA (Casanova et al 2011). However, depletion of PCL2 also affected PRC2 recruitment at target sites other than Xi, suggesting a more general function in PRC2 binding to chromatin.…”
Section: Polycomb Recruitment By Xist Rnamentioning
confidence: 99%
“…37 Primary sequence analysis reveals the presence of Tudor and PHD domains, which may bind to modified histones. Recent studies 38,39 have shown that the second PHD domain of MTF2 was required for targeting the PRC2 complex in ESCs. Previous studies have also shown that the PHF1 increases activity of the PRC2 complex in somatic cells.…”
Section: Effect Of Histone H1 Modifications On Prc2 Activity and Chromentioning
confidence: 99%